Validating a Collaborative Writing Competence Framework for EFL Instruction: A Confirmatory Factor Analysis Approach - Mujiono; Weganofa, Riza; Herawati, Siane; Lutviana, Rizky (Universitas Hamzanwadi, 2025)
Collaborative writing is widely recognized for its benefits in enhancing linguistic competence, critical thinking, and social interaction in EFL contexts. Despite numerous studies highlighting these advantages, a gap remains in how collaborative writing competence can be systematically assessed and practically applied in classroom settings. This study aims to empirically validate a Collaborative Writing Competence Framework (CWCF) comprising five key dimensions: communication, coordination, creativity, responsibility, and reflection. A quantitative research design involved 103 Indonesian undergraduate EFL students enrolled in an Essay Writing course. Data were collected using a Likert-scale questionnaire and analyzed through Confirmatory Factor Analysis (CFA). The model demonstrated a good fit (χ² = 86.528, df = 81, p = .317; CMIN/DF = 1.068; RMSEA = 0.026; CFI = 0.992), with acceptable reliability (Cronbach’s α = 0.719–0.807) and convergent validity (AVE = 0.501–0.673). Creativity emerged as the most influential factor in collaborative writing competence. The validated CWCF offers actionable insights for EFL instruction: structured peer discussions, guided brainstorming, and task delegation can enhance collaboration, while integrating self- and peer-assessment fosters responsibility and reflection. Digital platforms such as Google Docs may also support real-time coordination and feedback. The CWCF thus serves as both an assessment instrument and pedagogical tool, paving the way for more effective collaborative writing practices in EFL classrooms.